2019
DOI: 10.1016/j.omtm.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Safety and Immunogenicity Trial of Recombinant Lactococcus lactis Expressing Human Papillomavirus Type 16 E6 Oncoprotein Vaccine

Abstract: The present study purposed to investigate the safety, tolerability, and immunogenicity of the therapeutic NZ8123-HPV16-optiE6 vaccine, following oral vaccination. The safety and tolerability were evaluated. Specific serum immunoglobulin G (IgG) and vaginal IgA antibodies were calculated by ELISA, and E6-specific IFN-γ-secreting T cells were counted by enzyme-linked immune absorbent spot (ELISpot) assay in cervical lymphocytes and PBMC samples. The vaccine was well tolerated, and no serious adverse effects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…They showed that oral consumption of recombinant L. casei in patients suffering from CIN3 can increase E7-specific cell-mediated immune responses in cervical lymphocytes [51]. Also, previous data, supporting the data published by Kawana et al, revealed that L. lactis vaccine, as for L. casei, can induce a systemic cell-mediated immunity which is weaker than mucosal cell-mediated immunity in the cervix and at mucosal inductive sites [49,50]. In agreement with reports by Iranian scientists regarding prophylactic and therapeutic role of recombinant L. lactis to fight against HPV-16, Korean researchers emphasized that oral immunization with L. casei vaccine harboring a modified HPV-16 E7 antigen (BLS-M07) can induce protective humoral immune responses via generating HPV-16 E7-specific IgG plasma antibody [52].…”
Section: Clinical Trial Studies Of Hpv Vaccine Based On Labsupporting
confidence: 52%
See 2 more Smart Citations
“…They showed that oral consumption of recombinant L. casei in patients suffering from CIN3 can increase E7-specific cell-mediated immune responses in cervical lymphocytes [51]. Also, previous data, supporting the data published by Kawana et al, revealed that L. lactis vaccine, as for L. casei, can induce a systemic cell-mediated immunity which is weaker than mucosal cell-mediated immunity in the cervix and at mucosal inductive sites [49,50]. In agreement with reports by Iranian scientists regarding prophylactic and therapeutic role of recombinant L. lactis to fight against HPV-16, Korean researchers emphasized that oral immunization with L. casei vaccine harboring a modified HPV-16 E7 antigen (BLS-M07) can induce protective humoral immune responses via generating HPV-16 E7-specific IgG plasma antibody [52].…”
Section: Clinical Trial Studies Of Hpv Vaccine Based On Labsupporting
confidence: 52%
“…To address these shortcomings, in recent years, the next generations of HPV vaccines including LAB-based HPV vaccines have been developed and reached the clinical trial studies. Their results indicated that this type of vaccines can elicit both potent humoral and mucosal immune responses against E6 and E7 transforming proteins [49][50][51][52][53]. Data from preclinical studies [20,35] supported the results of phase I clinical trials of Iranian researchers and reported that L. lactis vaccines could produce HPV-16 specific serum-IgG and vaginal-IgA antibodies, along with CTL response in PBMCs and vaginal discharge of sexually active healthy females.…”
Section: Clinical Trial Studies Of Hpv Vaccine Based On Labmentioning
confidence: 77%
See 1 more Smart Citation
“…Viral, bacterial, and parasitic antigens have been expressed in L. lactis, and recombinant strains have been shown to be capable of delivering antigens at the intestinal mucosal sites, inducing a specific immune response in mice [23,24]. It has also been demonstrated that L. lactis can survive passage through the gastrointestinal tract in animals and human volunteers without colonizing it, which makes it a good candidate for vaccines in humans [25][26][27]. Immunization with L. lactis has advantages due to the vaccine adjuvant properties of its peptidoglycan wall and can also be used as a protein expression system that ensures the expression of the antigen [28].…”
Section: Introductionmentioning
confidence: 99%
“…101 This oral vaccine (NZ8123-HPV-16-optiE6) was moved to a Phase I study with 46 healthy volunteers for dose-escalation, tolerability, and safety. 102 No significant AEs were reported, and a dose-dependence was observed for humoral and persistent cell-mediated responses. Lactobacillus casei has been used for early in vivo work using L. casei expressing HPV16 E7, and another strain of L. casei expressing HPV16 E6.…”
Section: Lactobacillus-based Vectorsmentioning
confidence: 96%